Necrotizing myositis case report and brief literature study. Issue 6 (1st November 2020) - Basso, Arthur; Moerman, Filip; Ronsmans, Christophe; Demarche, Martine
ABSTRACT: Necrotizing myositis is an extremely rare soft tissue infection, mainly caused by Group A Streptococci. Although its presentation is nonspecific and seems harmless, it quickly leads to death in almost all cases. Therefore, diagnosis and treatment of necrotizing myositis are considered as medical emergencies. The 27 years old patient we report benefited from early diagnosis and care. Necrotic tissues were surgically removed 24 hours after the appearance of the first clinical signs. Intravenous antibiotherapy as well as immunoglobulin therapy were also given on the first day. Starting from this clinical case, we present a brief explanation of the pathogenesis, the key clinical features and appropriate tools for diagnosis. Then, adequate antibiotherapy, role of immunoglobulin therapy and interest of hyperbaric oxygenotherapy will be discussed.